Prognostic significance of α‐ and β2‐adrenoceptor gene expression in breast cancer patients - Rivero, Ezequiel Mariano (2019)
Breast cancer is the most frequently diagnosed and leading cause of cancer death among women worldwide. It was classified within molecular intrinsic subtypes: luminal A, luminal B, human epidermal growth factor receptor 2‐enriched and basal‐like. Epinephrine and norepinephrine, released during stress, bind to adrenoceptors. α2‐adrenoceptors are encoded by the ADRA2A , ADRA2B and ADRA2C genes and β2 by ADRB2 .